2021
DOI: 10.1017/ehs.2021.23
|View full text |Cite
|
Sign up to set email alerts
|

He for she? Variation and exaggeration in men's support for women's empowerment in northern Tanzania

Abstract: Achieving gender equality fundamentally requires a transfer of power from men to women. Yet data on men's support for women's empowerment (WE) remains scant and limited by reliance on self-report methodologies. Here, we examine men's support for WE as sexual conflict trait, both via direct surveys (n=590) and indirectly by asking men's wives (n=317) to speculate on their husband's views. Data come from a semiurban community in Mwanza, Tanzania. Consistent with reduced resource competition and increased exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…Only a handful of eligible couples refused to take part (3.7% of all couples contacted). Further information on sampling can be found in Lawson et al, 2021b.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a handful of eligible couples refused to take part (3.7% of all couples contacted). Further information on sampling can be found in Lawson et al, 2021b.…”
Section: Methodsmentioning
confidence: 99%
“…Women also frequently self-report greater acceptance of IPV than men, particularly in regions where IPV is most prevalent; indicating that men often hide their true attitudes as they are aware of the socially desirable response (Sardinha & Nájera Catalán, 2018; Tran et al, 2016; Uthman et al, 2009). Therefore, we chose a priori to rely on wives’ reports on their husbands’ attitudes, as we believe this best limits the impact of social desirability bias and provides a more reliable measure of husband’s condonement of IPV (for further justification of our approach see Lawson et al, 2021b). Wives’ responses were used to form a binary measure of husband’s condonement of IPV; the variable is coded 1 if women reported that their husbands would agree or strongly agree with either statement and 0 otherwise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Education was lower among those married early, but community members reported strong taboos against marrying school girls, suggesting that school dropout generally precedes marriages, rather than marriage taking girls out of school (Schaffnit, Hassan, et al, 2019). Consistent with gendered conflict, women report marrying somewhat older men than they would ideally prefer, but relatively larger husband-older spousal age gap was not predictive of marital stability or women's self-reported autonomy in decision making, self-reported experience of depression or reproductive success (Lawson, Schaffnit, Kilgallen et al, 2021).…”
Section: Introductionmentioning
confidence: 87%